2011
DOI: 10.1128/aac.05236-11
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Dapsone-Resistant Leprosy Detected by Molecular Epidemiological Approaches

Abstract: Drug resistance surveillance identified six untreated leprosy patients in the Philippines with Mycobacterium leprae folP1 mutations which confer dapsone resistance. Five patients share a village of residence; four who carried the mutation, Thr53Val, were also linked by M. leprae variable-number tandem repeat (VNTR) strain types. In India, folP1 mutations were detected in two relapse patients with a history of dapsone treatment. Mutations were not found in the rifampin target gene rpoB. These findings indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…There is only one report for this mutation type (24), which incidentally was detected in the same studied population, i.e., leprosy patients in Cebu, Philippines. The identification of multiple cases with this mutation in our study sample was due to transmission within a closely linked community, as captured and described in greater detail by Li et al by prospective molecular epidemiological approaches (18,30,31). Singh et al recently reported a method based on TaqMan probe assays for rpoB and folP1 (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is only one report for this mutation type (24), which incidentally was detected in the same studied population, i.e., leprosy patients in Cebu, Philippines. The identification of multiple cases with this mutation in our study sample was due to transmission within a closely linked community, as captured and described in greater detail by Li et al by prospective molecular epidemiological approaches (18,30,31). Singh et al recently reported a method based on TaqMan probe assays for rpoB and folP1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…The gyrA DRDR had not been sequenced. This sequence-based survey detected mutations in folP1 but not in rpoB DRDRs (18). The folP1 mutation types found were a codon 55 mutation (CCC¡CTC) (n ϭ 1) and a codon 53 mutation (ACC¡GTC) (n ϭ 3).…”
Section: Development Of Drdr Assays Based On Real-time Pcr-hrmmentioning
confidence: 99%
See 2 more Smart Citations
“…Two types of strain typing markers- variable number of tandem repeats (VNTRs) and single nucleotide polymorphisms (SNPs) that provide a range of resolution have been discovered and applied for different epidemiological questions (Groathouse et al, 2004; Zhang et al, 2005; Shin et al, 2000; Kimura et al, 2009; Srisungnam et al, 2009; Monot et al, 2005; Truman et al 2011). These applications include identification of family and community transmission clusters of leprosy and their evolution in geographic space, time and ethnicity (Weng et al, 2011; Sakamuri et al, 2009), the origin and global spread of leprosy (Matsuoka et al, 2006; Monot et al 2005), the surveillance of drug resistance (Maeda et al, 2001; Singh et al, 2011) and detection of clusters of resistant cases ( Li et al, 2011), distinction of relapse from re-infections and mixed infections (da Silva Rocha et al, 2011; Sakamuri et al, 2009; Weng et al, 2011), and for obtaining evidence for zoonosis ( Truman et al, 2011) and ‘reverse zoonosis or anthoponosis’ (Suzuki et al, 2010). …”
Section: Introductionmentioning
confidence: 99%